2015
DOI: 10.4155/fmc.15.23
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Antischistosomal Activity

Abstract: In recent years, natural product groups have been gaining prominence as possible sources of new drugs for schistosomiasis. This review attempts to update the antischistosomal natural compounds, or natural product-derived compounds, from the mid-1980s. Some of the main metabolites obtained from plants (e.g., terpenes, alkaloids, phenolic compounds and peptides) with in vitro and/or in vivo antischistosomal properties are discussed. Less thoroughly, due to scarcity of data in the literature, molecules from anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 105 publications
(247 reference statements)
3
51
0
Order By: Relevance
“…Therefore, widespread emergence of drug resistance is probable and makes the development of new therapeutic approaches against schistosomiasis mandatory. In the past years, numerous natural products and synthetic drugs have been evaluated as potential schistosomicidal agents [18,19], but few studies have shown the effects of these drugs on the induction of apoptosis in this parasite. Curcumin (CUR), a secondary metabolite of turmeric derived from C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, widespread emergence of drug resistance is probable and makes the development of new therapeutic approaches against schistosomiasis mandatory. In the past years, numerous natural products and synthetic drugs have been evaluated as potential schistosomicidal agents [18,19], but few studies have shown the effects of these drugs on the induction of apoptosis in this parasite. Curcumin (CUR), a secondary metabolite of turmeric derived from C .…”
Section: Discussionmentioning
confidence: 99%
“…Such new drugs could be potentially applied in the treatment of neglected tropical diseases (NTD), including schistosomiasis [18,19]. Curcumin (1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6 heptadiene-3,5-dione) (CUR) is the major curcuminoid compound extracted from Curcuma longa L., a plant that possesses many pharmacological and biological activities [20], including antiparasitic action [2125].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an extensive attention to natural products as a treatment of neglected tropical diseases, including schistosomiasis, has been growing. The awareness has stimulated an exertion to improve a new medicine as a substitute method to this parasitosis control [9, 10, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…The research on medicinal plants is encouraged by the WHO, considering that certain traditional knowledge on curative plants could add up to the development of new pharmaceutical products as well as to the combat against diseases that affects the populations of developing countries [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, many compounds with promising antischistosomal properties have been identified by academia (5). Among these, piplartine (piperlongumine) and curcumin have also been described as promising anticancer agents (6,7).…”
mentioning
confidence: 99%